Effect of Population Proportion of Component Crops on Growth, Yield and Nutrient Uptake of Component Crops in Maize+Soybean Intercropping - Telkar, S. G.; Singh, A. K.; Dey, Joy Kumar (International Journal of Bio-resource and Stress Management, 2017)
A field experiment was conducted during Kharif 2016 at CPGS, CAU, Umiam, Meghalaya. The soil was sandy clay loam in texture, moderately acidic in reaction (pH 5.23), high in soil organic carbon (1.02 %) and medium in available N, P and K (315.04, 16.34 and 196.12 kg ha-1, respectively). The experiment consist of eight treatments such as sole maize, sole soybean, 1:1replacement, 1:1additive, 2:1replacement, 2:1additive, 2:1paired and 2:2paired) replicated thrice in randomized block design. Sole maize recorded significantly higher yield attributes such as cob weight plant-1, grains cob-1 and grain weight plant-1 which was at par with 1:1Replacement but significantly superior over the all other treatments. However, 1:1Replacement for soybean recorded significantly higher yield attributes such as no. pods plant-1 and pod weight plant-1 which was at par with sole soybean and 2:1Replacement, 2:2Paired and 2:1Paired but significantly superior over the 1:1Additive and 2:1Additive. Among the intercropping treatments, significantly higher grain yield of maize recorded from 2:1Additive over grain yield recorded from all other intercropping except 2:1Replacement. In soybean, 1:1Replacement recorded significantly higher grain yield over all other intercropping treatments except 2:2Paired. Among the intercropping treatments, significantly lower N, P and K uptake by 1:1Replacement of maize than 2:1Additive, 2:1Replacement and 2:1Paired intercropping treatments. However, 1:1Replacement of soybean recorded significantly higher N, P and K uptake over the1:1Additive, 2:1Replacement, 2:1Additive, 2:1Paired and 2:2Paired intercropping treatments. From the results of this study concluded that 1:1Replacement intercropping of maize+soybean was more benefitted than any other intercropping treatments.